2015
DOI: 10.1016/j.addbeh.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring inhibitory processes for alcohol-related attentional biases: Introducing a novel attentional bias measure

Abstract: Results suggest that attentional bias is not just a process of stimuli becoming prioritised, but also stimuli becoming compulsory to attend and process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 39 publications
2
47
1
Order By: Relevance
“…Overall, these findings suggest that social drinkers may find it comparatively easier to detect both alcoholic and non-alcoholic appetitive targets when these are contrasted with non-appetitive distractors, perhaps because these stimuli are imbued with incentive value (see Monk et al 2017). Complementing previous research using indirect behavioural measures, the current research may therefore provide a more nuanced insight into unconscious AB processes (Jonides 1981;Mogg et al 2003;Wilcockson and Pothos 2015), suggesting further that AB towards alcoholic stimuli may generalise to other palatable non-alcoholic stimuli. The current research also included AUDIT and trait EC scores as covariates in light of research suggesting that individual differences in problem drinking and the inhibition of prepotent responding are related to alcohol-related AB (see Morales et al 2016;Posner et al 2014;Qureshi et al 2017;van Hemel-Ruiter et al 2015).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Overall, these findings suggest that social drinkers may find it comparatively easier to detect both alcoholic and non-alcoholic appetitive targets when these are contrasted with non-appetitive distractors, perhaps because these stimuli are imbued with incentive value (see Monk et al 2017). Complementing previous research using indirect behavioural measures, the current research may therefore provide a more nuanced insight into unconscious AB processes (Jonides 1981;Mogg et al 2003;Wilcockson and Pothos 2015), suggesting further that AB towards alcoholic stimuli may generalise to other palatable non-alcoholic stimuli. The current research also included AUDIT and trait EC scores as covariates in light of research suggesting that individual differences in problem drinking and the inhibition of prepotent responding are related to alcohol-related AB (see Morales et al 2016;Posner et al 2014;Qureshi et al 2017;van Hemel-Ruiter et al 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, drinkers have been shown to exhibit AB towards alcohol-related cues on the visual probe eye-tracking task (Fernie et al 2012;Miller and Fillmore 2010). Similarly, Wilcockson and Pothos (2015) found that increased alcohol use was related to the reallocation of attention from central fixation towards peripheral alcoholic stimuli (termed 'break frequency'). Research from both direct and indirect measures of AB therefore suggests that individuals who frequently consume alcohol might allocate attentional resources disproportionately towards alcohol-related stimuli.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 12 articles, it was shown that dependent drinkers have a higher attentional bias towards alcohol cues than nondependent controls (Carrigan et al 2004;Dickter et al 2014;Fadardi & Cox 2006, 2009Fridrici et al 2013;Garland et al 2012a,b;Lusher et al 2004;No€ el et al 2007;Sharma et al 2001;Townshend & Duka 2001;Wilcockson & Pothos 2015). Only two studies found no or a negative difference between respondents who are alcohol dependent and respondents who are not (Ryan 2002;Townshend & Duka 2007).…”
Section: Attentional Biasmentioning
confidence: 99%
“…In an effort to understand the exact role of such biases, researchers have employed different cognitive tasks (e.g., Jones & Schulze, 2000;Cox et al, 2006;Wilcockson & Pothos, 2015). Such work has led to several key insights regarding the nature of cognitive biases.…”
Section: How Cognitive Biases Can Distort Environmental Statistics: Imentioning
confidence: 99%